Digital policing in Nigeria: A study of Jigawa State Police Command - Ismail, Ukasha (International journal of police science & management, 2024)
The application of digital technologies in police practices can engender a number of benefits, which include round-the-clock surveillance, intelligence collection (in real time), community policing (through regular online briefings and trust-building by policing agencies) and disruption of crimes, among others. This study used situational crime prevention theory and examined the use, benefits and challenges of digital policing in Jigawa State Police Command, Nigeria. A sample of 230 respondents was utilized in the study. From the sample, 215 police personnel were administered questionnaires, and 15 in-depth interviews were conducted with 5 police personnel, 5 information technology professionals and 5 policing scholars. The study revealed that use of digital technologies in police practice is low in Jigawa State, because the study discovered insufficient digital technologies in the police command. Furthermore, the majority of police personnel sampled were not skilled in information and communications technologies. No doubt, poor use of digital technologies may pose a serious setback to crime prevention in Jigawa State, Nigeria. Therefore, it is recommended that the police should acquire and leverage on emerging policing technologies. Police personnel should be given adequate training and retraining on the use of digital technologies. Collaboration and information sharing with relevant agencies should also be improved.